PENGARUH EDUKASI VIDEO LATIHAN FISIK TERHADAP PENGETAHUAN PASIEN YANG MENJALANI HEMODIALISIS DI RS PKU MUHAMMADIYAH YOGYAKARTA - Ambar Relawati; Isnina Noor Sakinah; Rahmawati Dian Nurani (MEDIA ILMU KESEHATAN, 2018)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible kidney damage or dysfunction caused by the body's failure to maintain metabolism, fluid and electrolyte balance. Most of the CKD in Indonesia is diagnosed an advanced and late stage, so dialysis is necessary to solve this problem. The most common complaints of hemodialysis patients are muscle weakness. Patients with muscle weakness are due to reduced activity, muscle atrophy, muscle myopathy, neuropathy or a combination of them. One way that can be done as muscle strengthening to support and protect the internal organs and tissues is to do physical exercise. Physical exercises include flexibility exercises, strengthening exercises, and cardiovascular exercises. The exercise was done by giving video education to the patient for 60-90 minutes and 2 sets at the time of hemodialysis. Video is one of the educational media so that patients easily understand and imitate the steps of physical exercise. Objective: To know effectiveness of patient education with video to hemodialysis patient knowledge about physical activity exercise. Methods: This study used quasi experimental method with one-group design pre-post test design. Results: This research is a non parametric statistic test with Wilcoxon test method and got the result of 0.000 (p<0,05). Conclusions: Video education can improve the knowledge of patients with chronic renal failure who run hemodialysis. Keywords: Chronic Kidney Disease (CKD), hemodialysis, Physical Exercise, Video Education.